A two-player game system implemented under WAP. (5th January 2005) - Warren, Andrew; Excell, Peter S.; Wyatt-Millington, William
The implementation of a two-player interactive game on WAP-enabled mobile phones is described. The game is played over the network, using a server as a neutral host, and to maximise compatibility and market size the game is designed to be playable even with low-performance terminals (WAP 1 over non-GPRS GSM). The system was constructed using UML to give a high-level structure to the development process. Test results for typical WAP 1.1 phones are listed and the inherent problems of browser-based programs are discussed. The advantages and shortcomings of future technologies are discussed, in the context of the wider spectrum of multi-user applications.